Determinan kebijakan dividen dalam perspekif kinerja keuangan - Gretalia Firanti Kakiay; Diana Nova Lintong (Yayasan Widyantara Nawasena Raharja, 2026)
This study investigates the effect of financial performance on dividend policy in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Financial performance is proxied by profitability (Return on Assets), liquidity (Current Ratio), and leverage (Debt to Equity Ratio), while dividend policy is measured using the Dividend Payout Ratio. Employing a quantitative associative approach, this study analyzes secondary data obtained from annual financial statements of nine firms selected through purposive sampling, resulting in 36 firm-year observations. Multiple linear regression is used to test the proposed relationships. The empirical results indicate that profitability and liquidity do not have a significant effect on dividend policy, whereas leverage has a negative and significant effect. These findings suggest that firms with higher debt levels tend to prioritize debt repayment over dividend distribution. This study contributes to the dividend policy literature by providing empirical evidence from the post-pandemic period and highlighting the dominant role of leverage in dividend decisions within Indonesia’s property and real estate sector.